Current trends in the biokinetic analysis of the foot and ankle - Metsavaht, Leonardo; Leporace, Gustavo (Journal of the Foot & Ankle, 2020)
Although the importance of studying the anatomy of structures of the ankle and foot joints is fundamental, evidence points to a low correlation between static and dynamic measurements; this could represent a problem in the study of the functioning of the ankle and foot during daily activities. The aim of the present study is to review the classic knowledge on ankle and foot biomechanics and present new concepts of functional biomechanics (3-dimensional biokinetic analysis) in order to clarify their clinical applications in assisting diagnostic and/or treatment decisions. For this, we performed a literature review and divided the article into 6 sections: (1) functional biomechanics of the ankle and foot; (2) dynamic joint stability; (3) functional stability mechanisms of the foot; (4) functional stability mechanisms of the ankle; (5) gait and running biokinetics; (6) the role of proximal joints in ankle and foot movement. At the end of this article, the reader should be able to understand how the 3-dimensional biokinetic analysis of the ankle and foot can contribute along with imaging examinations to the clinical setting, thus allowing the construction of a more complete profile of the patient. Such information could enable the identification of weaknesses and the implementation of objective interventions for each patient. Level of Evidence V; Prognostic Studies; Expert Opinion.